Influence of time of planting and spacing on yield and quality of turmeric (Curcuma longa l.) in terai region of West Bengal - Mandi, Sunil; Saha, Partha; Saha, Namita Das; Bindu, J Poorna; Barman, JK Roy; Nambari, Ramu; Dam, SK; Satyanarayana, K; Krishna, S Kasturi (Current Horticulture, 2025)
The turmeric productivity in West Bengal is very low (2.5 t/ha) as compared to national productivity (4.7 t/ha) and this is mainly because of poor knowledge of the farmers about suitable production technology. The present field study was conducted to evaluate the performance of turmeric (Megha Turmeric-1) under different planting time and spacing combinations in Terai region of West Bengal. The experiment was laid out in split plot design with three replications. The observations were recorded for different parameters like plant height, number of leaves per plant, total rhizome weight, primary rhizome weight, primary rhizome length, primary rhizome girth, primary rhizome width, fresh rhizome yield per hectare and curcumin content. The date of planting had more effect on different parameters as compared to spacing. The highest total rhizome weight (229.4 g), primary rhizome weight (94.8 g), primary rhizome length (8.1 cm), primary rhizome girth (5.8 cm) and primary rhizome diameter (1.0 cm), fresh rhizome yield (18.6 t/ha) was recorded when planting was done on first fortnight of April. Spacing had significant role on other rhizome parameters like primary rhizome weight, primary rhizome length, girth and diameter. There was increasing trend of primary rhizome weight when spacing was increased. The highest primary rhizome weight (74.1 g) was observed when the rhizome was planted at a distance of 50×30 cm whereas in 30×30 cm spacing it was 55.0 g. However, highest fresh rhizome yield (19.2 t/ha) was observed in 30×30 cm spacing. All the morphological and yield parameters significantly varied with combined effect of time of planting and spacing. The fresh rhizome yield per hectare and curcumin content were higher in case of interaction effect than the individual effect of time of planting and spacing. The highest yield (24.3 t/ha) was obtained in first fortnight of April planting with 30×30 cm spacing. Therefore, for obtaining higher yield and high cucumin, the first fortnight of April planting at 30×30 cm spacing can be recommended as suitable production technology for turmeric (Megha Turmeric-1) in Terai region of West Bengal.